Seasonal variations in the mental state and heart rate variability in adolescents residing beyond the Arctic Circle - Natalia K. Belisheva; Alla A. Martynova; Sergei N. Kolomeichuk (Russian Open Medical Journal)
Background — Residence beyond the Arctic Circle is associated with a distinct condition, Polar Tension Syndrome (PTS), which shares similarities with Seasonal Affective Disorder (SAD). However, the interplay of mental state and heart rate variability within the context of seasonal photoperiodicity in both PTS and SAD remains poorly understood. Objectives — This study investigated the effects of polar photoperiodicity on the mental and physiological states of male adolescents living in the Kola Peninsula, Russia (67°34′ N, 33°23′ E), a region beyond the Arctic Circle. Methods — Mental state was assessed using the State-Trait Anxiety Inventory (STAI) and the Self-Esteem of health, Activity, and Mood (SAM) scales. Heart rate variability (HRV) indices provided objective measures of the psychophysiological state. Results — Significant associations were found between state and trait anxiety (StA and TrA) and seasonal photoperiodicity in adolescents residing beyond the Arctic Circle. Reduced parasympathetic (HF) and increased sympathetic (LF) Autonomic Nervous System (ANS) contributions to heart rate (HR) regulation during the polar night may underlie the physiological manifestations of polar tension syndrome (PTS) and seasonal sffective disorder (SAD), both characterized by elevated anxiety. Analysis revealed monthly fluctuations in the dominance of HF and LF contributions to HR regulation, with LF predominating during the polar night and in March. Conclusion — This study demonstrates an association between state and trait anxiety (StA and TrA), heart rate regulation, and seasonal photoperiodicity in adolescents residing beyond the Arctic Circle. Adolescents with anxiety and low parasympathetic (HF) HRV activity show an increased risk of developing PTS and SAD symptoms.